2015
DOI: 10.3390/children2010039
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Play Environment after a Disaster: The Great East Japan Earthquake

Abstract: The Great East Japan Earthquake of March 11, 2011, together with the subsequent tsunami and nuclear power station accident, damaged a wide area of land. Children who experienced these terrible disasters and the post-disaster situation are still suffering in mental, physical and social ways. Children’s play is an activity that they undertake naturally and which can help them recover from such disasters. This paper addresses the role of play, adventure playgrounds and other play interventions, including play bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…(p. 7) This again reflects the compensatory aspect of the purpose of playwork by providing the space and opportunities for children to play. One example of how this was put into practice was in Japan where the use of adventure playgrounds provided space and opportunities for children and young who experienced earthquakes and Tsunami to play (Kinoshita & Woolley, 2015). Another example where the process of play was used to support children in Romanian orphanages (Brown & Webb, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(p. 7) This again reflects the compensatory aspect of the purpose of playwork by providing the space and opportunities for children to play. One example of how this was put into practice was in Japan where the use of adventure playgrounds provided space and opportunities for children and young who experienced earthquakes and Tsunami to play (Kinoshita & Woolley, 2015). Another example where the process of play was used to support children in Romanian orphanages (Brown & Webb, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Stress and an increase in alcohol consumption were considered to be other environmental factors that impacted cleft birth prevalence after Hurricane Katrina (Goenjian et al, 2011). Increases in stress, including post-traumatic stress disorder, depression, and sleep disturbance, were also reported in Miyagi Prefecture after the 2011 Tō hoku earthquake and tsunami (Fujihara et al, 2012;Fushimi, 2012;Tuerk et al, 2013;Kinoshita and Woolley, 2015;Onose et al, 2015;Sakuma et al, 2015;Fujiwara et al, 2017;Sakurai et al, 2017;Xu et al, 2018;Yabe et al, 2018;Inoue et al, 2017). Some reports described deteriorating liver function due to an increase in alcohol consumption (Nakanishi et al, 2014;Murakami et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Electric cables and water supply structures were catastrophically damaged, resulting in a severely deteriorated quality of life. There have been many reports regarding the disaster's impact on human health, including physical (Nakano et al, 2012;Itabashi et al, 2014;Sakurai et al, 2016;Hayashi et al, 2017;Sado et al, 2018) and psychological problems (Fujihara et al, 2012;Fushimi, 2012;Tuerk et al, 2013;Kinoshita and Woolley, 2015;Onose et al, 2015;Sakuma et al, 2015;Fujiwara et al, 2017;Sakurai et al, 2017;Xu et al, 2018;Yabe et al, 2018;Inoue et al, 2017). The impact on regional birth outcomes has also been studied; it has been reported that the incidences of preterm birth and low birth weight were not adversely affected by the disaster (Sugawara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In their 2015 study, Kinoshita and Woolley found that adventure playgrounds helped to relieve mental stress, particularly in overcoming shocking natural events such as earthquakes and tsunamis. This is because children are not the same as adults in expressing their emotions, and their mental health care should not be ensured with just a counsellor, but also through play environments as well [41].…”
Section: Structural Designsmentioning
confidence: 99%